2022
DOI: 10.1007/s10845-022-02007-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing additive manufacturing and mass customization under capacity constraints

Abstract: Additive manufacturing (AM), originally used for prototyping, is increasingly adopted for custom final part production across different industries. However, printing speed and production volume are two barriers for the adoption of AM for product customization at large scale. Nevertheless, manufacturers could aim to combine the benefits of AM for product customization with traditional mass customization (MC) technologies over the product life cycle (PLC). This approach is showcased in our paper as a manufacturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, they concluded that the widespread use of 3D printers would address supply chain design challenges. J. Ma et al [16] have studied a case study for home appliance after sale services using 3D printing on mobile stations that results confirmed the applicability and effectiveness of the proposed model. [17] have designed an AM supply network and choose between printing upon demand and sourcing through an alternative option for each part in each set.…”
Section: -Introductionmentioning
confidence: 55%
“…However, they concluded that the widespread use of 3D printers would address supply chain design challenges. J. Ma et al [16] have studied a case study for home appliance after sale services using 3D printing on mobile stations that results confirmed the applicability and effectiveness of the proposed model. [17] have designed an AM supply network and choose between printing upon demand and sourcing through an alternative option for each part in each set.…”
Section: -Introductionmentioning
confidence: 55%
“…This transformative technology has opened new avenues for design, production, and innovation by enabling the layer‐by‐layer construction of intricate and complex structures. AM provides numerous benefits such as customization/personalization at lower cost and rapid delivery, [ 1 ] decentralized and on‐demand manufacturing, [ 2 ] and material saving and minimized waste, [ 3 ] to name a few. In particular, during the Covid pandemic the localized on‐demand production of personal protective equipment as well as crucial medical parts exhibited the advantages of AM at the situation of the logistics and supply chain disruption and high demands on rapid delivery.…”
Section: Introductionmentioning
confidence: 99%